Phytochemical analysis, Anti inflammatory activity, in vitro antidiabetic activity and GC-MS profile of Erythrina variegata L. bark - Nagaraj Santhiya,Suriyamoorthy Priyanga,Subrhamanian Hemmalakshmi,Kanakasabapathi Devaki (Journal of Applied Pharmaceutical Science, 2016)
Many beneficial medicinal products are used to treat various serious diseases and disorders like diabetes, cancer and cardiovascular diseases without side effects. Hence our study focused to investigate the phytochemical analysis, quantification of bioactive compounds (alkaloid, phenols, flavonoids), in vitro free radical scavenging activity, anti-inflammatory activity (Membrane stabilization assay), in vitro anti-diabetic activity by enzyme inhibition activity, glucose uptake assay in isolated rat hemi-diaphragm and in yeast cells and also record GC-MS profile of Erythrina variegata L. bark (methanolic extract) which has boundless medicinal properties. The results of this study showed the evidence that the extracts when tested for their phytochemicals and free radical scavenging activity were found to have considerable antioxidant potential. This plant also exhibit better in vitro enzyme inhibitory activity, inhibition of non- enzymatic glycosylation of hemoglobin, in vitro anti-diabetic activity proved by glucose uptake assays and anti-inflammatory activity. GC-MS analysis of methanolic extract of Erythrina variegata L. bark revealed the presence of 58 compounds which are responsible for pharmacological activities. The results of this study indicate that the methanolic extract of Erythrina variegata L. bark has significant pharmacological properties.
Keywords: E. variegata,Phytoconstituents,DPPH,Glycosylation of hemoglobin,GC-MS.